FORMULASI STRATEGI KORPORASI DALAM KETIDAKPASTIAN MASA DEPAN PASCA COVID-19 - Edon Ramdani (JURNAL AKUNTANSI BARELANG, 2020)
The Covid-19 virus which has swept the world and become a global pademic has changed the world order. The reduced social economic activities of the community to reduce social interaction that can accelerate the spread of the virus, resulting in a decline in the performance of economic sectors. Many industries experience a decline in revenue and can result in further cessation of company operations. Pademi Covid-19 to date has not been able to predict how long it will end which causes uncertainty about the future. In order for a company to continue to exist and grow sustainably, it is very important to formulate a future strategy that is full of uncertainty. In this article, we review strategies options that can be applied to various levels of uncertainty. In the future uncertainty, the leadership of the company is demanded to be more courageous in making strategic decisions. From a variety of alternative strategy choices, in order to deal with the difficult conditions at the moment, the initial theory regarding investment management can be considered in the form of a business diversification strategy. So that the risks experienced can be spread in various fields of business / industry not only in one business, as the theory of the father of investment management Herry Markowizt "don't put all your eggs in one basket".